The Race for Innovation in the Media and Content Industries: Legacy Players and Newcomers: Lessons for Policy Makers from the Video Game and Cinema Industries. - Benghozi, Pierre-Jean; Salvador, Elisa; Simon, Jean-Paul (Journal of Arts Management, Law & Society, 2017)
How do media industries innovate? How can they compete with powerful competitors from the information technology world? The article focuses on the video game and cinema industries. The findings reveal their contrasting specific forms of innovation and provide a fresh understanding of its twofold nature in these industries. It does not boil down to simply creating new content but is increasingly open to the investment and integration of technologies. The evolution of the development models and the changes brought by technology raise questions about how to (re)consider the role of public intervention in these industries.